The Experience of OFF Periods in Parkinson’s Disease: Descriptions, Triggers, and Alleviating Factors - Sneha Mantri; Madeline Lepore; Briana Edison; Margaret Daeschler; Catherine M. Kopil; Connie Marras; Lana M. Chahine (Journal of Patient-Centered Research and Reviews, 2021)
Purpose: Wearing off of Parkinson’s disease medication is common, but triggers and coping strategies for this transient phenomenon are poorly understood. We aimed to assess the lived experience of OFF periods for people with Parkinson’s disease.